مفهوم الأذى وانواعه في القرآن الكريم – دراسة موضوعية - قسوم, ليلى (University of Eloued جامعة الوادي, 2017)
فقد اخترت هذه الدراسة بعنوان: مفهوم الأذى وأنواعه في القرآن الكريم، حيث قسمتها إلى مقدمة، احتوت أهمية الموضوع، وأهدافه، والمنهج المتبع، وكذا الدراسات السابقة، وطرح الإشكال. كما احتوت الدراسة بيان مفهوم الأذى في اللغة والشرع وكذا اشتقاقاته وصيغه الواردة في القرآن الكريم. وتناولت فيها أيضا أنواع الأذى في القرآن الكريم، حيث ينقسم إلى نوعين:النوع الأول:الأذى الحسي ويتمثل في الأذى الملموس، حيث يشمل الأذى المحمود والمتمثل في إقامة الحد على مرتكبي الفاحشة، وكذا الأذى المذموم والمتمثل في أذية النبي وأذية المؤمنين والمؤمنات أما النوع الثاني: الأذى المعنوي وينقسم إلى قسمين الأذى باللسان والأذى بالقلب، ويشمل أذية المولى تبارك وتعالى، وأذية النبي ، وأذية المؤمنين والمؤمنات. ثم تطرقت إلى ذكر أهم السياقات التي ورد بها الأذى في القرآن الكريم، وفي الأخير، فقد خصصته لذكر أنجع سبل مدافعة الأذى وعلاجه، ثم ختمت بحثي بخاتمة أوجزت فيها ما فصلته، وبينت أهم النتائج والتوصيات. I chose this study entitled: The notion of prejudice and types in the Koran, where it divided into the introduction, contained the importance of the subject, and its objectives, and the approach, as well as previous studies, bring confusion The study also contained a statement of the prejudice in language and Shara, as well as Achtqaqath and the formula contained in the Quran He also dealt with the types of misdeeds in the Qur'an, which is divided into two types: the first type: mal-sensory and harming the concrete, which includes poor Mahmoud, to establish the limit of the perpetrators of scandalous, as well as damage Blameworthy and Allenba dommages damages and harm believers, men and women The second type: the moral damage is divided into two parts harm the language and evil to the heart, and includes damage to God Almighty, prophet and evil and believe men and women a prejudice. With reference to the most important contexts in which the evil reported in the Quran, and in the Qur'an, he mentioned the most effective means of pleading for damages and treatment, and then concluded a conclusion of Which summarizes what was rejected, and showed the most important findings and recommendations
مذكرة ماستر تخصص تفسير وعلوم قرآن
Keywords: الأذى الله – أنواع الأذى – مفهوم- صيغ الأذى; Damage to Allah - Types of Damage - Prejudice Formulas Mvhom-